Patient perspectives on cervical cancer screening interventions among underscreened women - Andrea C. Des Marais; Noel T. Brewer; Suzanne Knight; Jennifer S. Smith (PLoS ONE, 2022)
Background Cervical cancer is highly preventable with regular screening, yet over 4,000 women die from it annually in the United States. Over half of new cervical cancer cases in the U.S. are attributable to insufficient screening. Methods Participants were 23 low-income, uninsured or Medicaid-insured women in North Carolina who were overdue for cervical cancer screening according to national guidelines. Semi-structured interviews examined perspectives on barriers to cervical cancer screening and on interventions to reduce these barriers. We also elicited feedback on three proposed evidence-based interventions: one-on-one education, coupons to reduce out-of-pocket costs, and self-collection of samples for detection of high-risk human papillomavirus (HPV) infection, the primary cause of cervical cancer. Results Reported barriers included high cost, inconvenient clinic hours, lack of provider recommendation, poor transportation, difficulty finding a provider, fear of pain, and low perceived need. Participants suggested interventions including reducing cost, improving convenience through community-based screening or extended clinic hours, strengthening provider recommendations, and providing one-on-one counseling and education outreach. HPV self-collection was most frequently selected as the “most helpful” of 3 proposed interventions (n = 11), followed by reducing out-of-pocket costs (n = 7) and one-on-one education (n = 5). Conclusion Cost was the most reported barrier to cervical cancer screening, although women experience multiple simultaneous barriers. Novel interventions such as HPV self-collection promise to reduce some, but not all, barriers to primary screening. Interventions that work on reducing multiple barriers, including obstacles to receiving follow-up care, may be most effective to prevent cervical cancer among these high-risk women.